On some common and new cavum-bearing Planothidium (Bacillariophyta) species from freshwater - Wetzel, C. E.; Van de Vijver, B.; Blanco, S.; Ector, L. (Fottea, 2019)
Thirteen Planothidium species are illustrated and discussed in a detailed morphological account based on light and scanning electron microscopy analysis of modern and historic materials related to the names Planothidium rostratum (Østrup) Lange–Bertalot and Planothidium frequentissimum (Lange–Bertalot) Lange–Bertalot. Eight species from freshwater environments in Europe, Asia and South America are proposed as new. All taxa here discussed and illustrated belong to the group of species characterized by the presence of a cavumin the rapheless valve. Additional information concerning their distribution and ecology is briefly commented based on a thorough literature revision